Historical information in Ibn Taymiyyah's writings : an exploratory study - Tijani, Ibraheem Musa (International Islamic University Malaysia. Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
This research highlights the historical views of Ibn Taymiyyah throughout his writings; with the aim of establishing whether he possesses authority on the historical issues he dealt with. The method used in this research, being an exploratory research, is to explore his intellectual background in the field and also his acquaintance with the various works and authors of this science. After which, his methods of criticizing historical narratives is analyzed to further show his consciousness of fabricated and false narratives attributed to historical incidents. Furthermore, to ascertain whether he should be included within the ranks of historians, the research compared his historical views with the “father of history” Ibn Khaldun from his Muqaddimah. Therefore, the aim of this exploratory study is not to presuppose Ibn Taymiyyah is like Ibn Khaldun in history but grant him acknowledgement for his contribution to the science of history, which could be applicable to scholars similar to him. The study shows that Ibn Taymiyyah is well-versed on historical events and their narratives. He was praised for his knowledge of history and even on historical narratives of Christianity, his approach was said to be unprecedented. On Greek history, his views are in line with modern historical discoveries. The findings of the research clearly shows that Ibn Taymiyyah was not among those who Ibn Khaldun criticized as scholars or traditionalists who were not critical of historical text that they narrated from others, but rather Ibn Taymiyyah himself expressed similar criticisms of narratives that Ibn Khaldun, who came after him, also criticized as historically false. In conclusion, Ibn Taymiyyah stands as a scholar of expertise in historical criticism throughout his writings.